2019
DOI: 10.1186/s12879-019-4092-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastroenteritis associated with Rotavirus A among children less than 5 years of age in Nepal

Abstract: Background Rotavirus gastroenteritis is a major public health problem in Nepal. This study was conducted to obtain information associated with Rotavirus gastroenteritis and to perform genotyping of Rotavirus A. Methods Hospital based cross sectional study was conducted from January to December 2017 among children less than 5 years of age attending Kanti Children’s Hospital and Tribhuvan University Teaching Hospital. Rotavirus A antigen detection was performed by Enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
3
12
3
Order By: Relevance
“…Diarrhea in our study was present in all infants 100%, which is identical with the study of Shresth et al (12). In the study of Karampatsas et al in London, diarrhea was reported in 86% of cases (13), and in the study by Arístegui et al, the incidence of diarrhea was 97% (14).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Diarrhea in our study was present in all infants 100%, which is identical with the study of Shresth et al (12). In the study of Karampatsas et al in London, diarrhea was reported in 86% of cases (13), and in the study by Arístegui et al, the incidence of diarrhea was 97% (14).…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Shresth et al, the infection was more prevalent in male (31%) than in female (24%) but without statistical significance (12). The results obtained by the RVGE analysis in London are compatible with our results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations